Rare bird documentation form for Peregrine Falcon at Sweet Marsh, 1984 - Moore, Francis L.et al (1984)
Rare bird documentation form for a Peregrine Falcon on the east side of Sweet Marsh in Bremer County, IA on April 15, 1984. Epson - sheet feed